Diversity of mollusks (bivalves and gastropods) in degraded mangrove ecosystems of Kolaka District, Southeast Sulawesi, Indonesia - Fajar Hasidu; Jamili Jamili; Gaby Nanda Kharisma; Arif Prasetya; Maharani Maharani; Riska Riska; La Ode Adi Parman Rudia; Akhmad Fadli Ibrahim; Azhar Aras Mubarak; La Ode Muhsafaat; Luthfi Anzani (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Hasidu LOAF, Jamili, Kharisma GN, Prasetya A, Maharani, Riska, Rudia LOAP, Ibrahim AF, Mubarak AA, Muhasafaat LO, Anzani L. 2020. Diversity of mollusks (bivalves and gastropods) in degraded mangrove ecosystems of Kolaka District, Southeast Sulawesi, Indonesia. Biodiversitas 21: 5884-5892. Mollusks are one of the mangrove organisms whose classes are bivalves and gastropods. It plays an important role in mangrove and marine ecosystems as filter feeders, predators, and herbivores. This study aims to knows the diversity and abundance of mollusks (bivalves and gastropods) in several mangrove ecosystems in the Kolaka coastline as well as the similarity of these locations. This study was conducted in mangrove ecosystems of Induha Village, Mangolo Village, Tahoa Village, and Towua Village of Kolaka District, Southeast Sulawesi, Indonesia, from July to August 2019. This is a transect method stretched along a 100 m line perpendicularly from the seaward. The size of the mollusks subplot was 1 m2 and placed along the line transect. Each line transect comprises 10 subplots. To analyze the diversity index, evenness index, and its abundance, Kaleida Graph 4.0 version was used. This research indicates that the mollusks consist of 4 families of bivalves with 6 species and 10 families of gastropods with 182 species. It also found out 23 species of mollusks scattered to each location. The molluscan species which spread in all four mangrove ecosystems were Terebralia sulcata, Nerita planospira, and Batillaria multiformis. In Induha, the mollusks species were Anadara notabilis and Drupella margariticola. Meanwhile, Saccostrea cucullata, Pirenella incisa, Clithon oualaniensis, and Clithon pulchellum were only found in Towua. The diversity index of bivalves in each location was categorized as low diversity index category, as well as gastropods were categorized as medium diversity index. The highest diversity index of gastropods was in Induha (H' = 1.96). It was supported by the good mangrove ecosystem for mollusks' habitat. The lowest diversity index of gastropods was in Towua (1.41). This research depicts that three kinds of species with high abundance rate whose rates were >1 ind/m2are located in two different locations namely; P. incisa (3.9 ind/m2) and S. cucullata (3.2 ind/m2) in Towua and followed by B. multiformis (2 ind/m2) and Isognomon ephippium (1.2 ind/m2) in Mangolo.